Entrepreneurship Mindset Training For Students of Mano Vocational School, West Manggarai, East Nusa Tenggara - Lena Ellitan; Lina Anatan (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
The younger generation has an important role in realizing Golden Indonesia 2045, therefore creativity and innovation are needed to support changes towards progress. In other words, the younger generation needs to have an entrepreneurial mindset that is able to create its own business field. Therefore, investment in education and training is necessary in developing an entrepreneurial mindset for the younger generation. This entrepreneurial mindset training activity was conducted on Mano Vocational School students who were undergoing an internship program at one of the plantations in Liang Ndara Village, West Manggarai, East Nusa Tenggara Province. The method of implementing service is divided into three activities including presentation of material from the speakers, focus group discussions (FGD), and sharing sessions. In general, service activities are conducted as an effort to transfer knowledge from academic sources to student interns on plantations to strengthen relations between academics and the world of business. In particular, service activities are conducted to provide an understanding of the importance of entrepreneurship, increase motivation, and foster an entrepreneurial mindset among students, the majority of whom are children of local farmers. Based on the evaluation results, it can be concluded that this activity conducted well and provided significant benefits for the participants so that it was deemed necessary to conduct further activities to support the younger generation in entrepreneurship.